1996
DOI: 10.1096/fasebj.10.9.8801181
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids in lung development

Abstract: The "retinoid revolution" has had considerable impact on research activity in the field of lung development. Postnatal lungs are very sensitive to dietary retinol (R) deprivation. The trachea and the bronchopulmonary tree in R-deficient animals show a striking change in morphology. The columnar epithelium undergoes keratinizing metaplasia, which is reversed when R is supplied. The fetal lung develops postnatally to become one of the most complex organs, characterized by 40 different cell types. The fetal lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 37 publications
(1 reference statement)
3
89
0
2
Order By: Relevance
“…The distance from one wall of the marked airspace to the opposite wall was measured using a ruler in the same orientation as the horizontal portion of the cross on the transparent grid. This dimension is the point-sampled intercept (1) and was used to calculate the volume of the individual airspaces using the formula l 3 /3. An average of 34 alveoli and 19 alveolar ducts or sacs were measured per animal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance from one wall of the marked airspace to the opposite wall was measured using a ruler in the same orientation as the horizontal portion of the cross on the transparent grid. This dimension is the point-sampled intercept (1) and was used to calculate the volume of the individual airspaces using the formula l 3 /3. An average of 34 alveoli and 19 alveolar ducts or sacs were measured per animal.…”
Section: Methodsmentioning
confidence: 99%
“…Retinoids regulate the development of the conducting airways and the gas-exchange portion of the lung (1). The major biologically active retinoid, all-trans retinoic acid, is a metabolite of retinol (vitamin A) (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, Massaro and Massaro (14) demonstrated that the inhibition of alveolarization produced by dexamethasone treatment of newborn rats could be attenuated by the administration of retinoic acid. In addition to antagonizing some actions of dexamethasone, retinoic acid has been shown to play a role in lung development (15)(16)(17)(18), and retinoids appear to participate in lung repair after hyperoxic injury (19,20).…”
mentioning
confidence: 99%
“…Retinoic acid (RA) exerts a profound effect on vertebrate development, cellular differentiation, and homeostasis [1][2][3][4]. In addition, RA plays a pivotal role in the induction and maintenance of mucociliary differentiation of airway epithelial cells [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%